Act, other instrument work of Inspection - Berengueras Pont, Mercè; Vera Mur, José María (Avances en Supervisión Educativa, 2014)
The paper aims to analyze and justify the act, as documentary work instrument of education inspectors, similarly as do other inspection professionals, work and finances.The conceptual and legal framework of the act as such, its public and documentary evidence, as well as subjective and formal aspects, and its implementation in the performance of the inspectors of education is analyzed, concluding with its distinguishing aspects regarding reports.Communication complements the statutory and regulatory references given in the regulatory provisions of the Education Inspectorate, both state and regional level.
Keywords: public administration; inspection; management; minutes